Severidade da incontinência urinária versus susceptibilidade ao desenvolvimento de disfunção sexual em mulheres - Brasil, Daniele Matos de Moura (2019)
The present study aims to analyze the relationship of urinary incontinence and sexual 1dysfunction in women from the ICIQ-UI / SF and FSFI instrument scores. This is a crosssectional study conducted at the Urogynecology Service of Maternidade Escola Assis Chateaubriand (MEAC), from September 2016 to February 2018. The sample inclusion criteria were: women aged 18 years or older, have stress or mixed urinary incontinence, and with a degree of pelvic organ prolapse less than or equal to 3 (POP-Q), active sex life in the last 4 weeks and who agreed to participate in the study. They totaled 85 women studied. Data were collected by applying the clinical history sheet, the Brazilian Economic Classification Criteria (CCEB) for class stratification, the International Consultation on Incontinence Questionnaire - Urinary Incontinence / Short Form (ICIQ-UI / SF) and the Female Function Sexual Index. (FSFI) and the application of two qualitative questions. Data analysis was performed with the aid of the Statistical Package for Social Sciences (SPSS), version 2.0 and the discourses analyzed regarding content analysis. Aspects of resolution 466/2012, which regulate scientific research with human beings, were respected. There was no correlation between the results of the questionnaires studied. The qualitative data brought a heterogeneous profile of responses, highlighting the role of the spouse as a fundamental strategy for the adaptation of women to sexual activity in the context of urinary loss. The approach of female sexuality in the context of urinary incontinence has specificities that can often transcend approaches proposed by validated questionnaires.